LOVE AND BETRAYAL IN THE SHADOW OF WAR: PAT BARKER'S REGENERATION TRILOGY - Waham, Jihad Jaafar (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2025)
This study examines the interconnected themes of love and betrayal within the psychological and moral framework of Pat Barker’s esteemed Regeneration Trilogy: Regeneration (1991), The Eye in the Door (1993), and The Ghost Road (1995). The objectives are threefold: first, to analyze the dual role of love as a therapeutic and disruptive force among individuals traumatized by war; second, to examine betrayal as a complex motif involving personal relationships, institutional authority, and ideological allegiance; and third, to evaluate how these emotional dynamics mirror the broader psychological disintegration and ethical ambiguity of wartime society. The methodology utilizes a qualitative literary analysis informed by psychoanalytic and historical frameworks, using trauma theory and war studies to elucidate the psychological complexity of Barker’s characters. Detailed textual analyses are enhanced by secondary critical sources that examine trauma, gender identity, and the politics of memory. The results demonstrate that Barker deconstructs traditional war narratives by highlighting psychological authenticity and emotional intricacy. Betrayal functions as a social and psychological mechanism that reveals the fissures within individuals, institutions, and the moral structure of wartime Britain. The discourse indicates that Barker's feminist and humanist viewpoints contest dominant notions of masculinity, loyalty, and patriotism. Through her intricate depiction of love and treachery, she examines the morality of survival and the vulnerability of human integrity in difficult circumstances. In conclusion, the study posits that Barker’s trilogy surpasses conventional war literature by converting personal feeling into a medium for historical and ethical contemplation.